Pelatihan Pengisian Sasaran Kinerja Dosen - HD. Melva Sitanggang; Lbn. Raja, Edward Alezndro; Tunggal Hasugian, Putra Raja (Jurnal Mitra Pengabdian Farmasi, 2023)
Lecturers as academic staff must always be equipped with knowledge and skills in carrying out their role as educational staff so they are not left behind in their duties. Lecturer performance planning must be planned from the start so that at the end of the implementation of the Tridharma of higher education each lecturer can carry out their duties properly as a form of their responsibility as educators. Completion of lecturer performance targets contains planning activities for each lecturer planned by each lecturer for one year starting at the beginning of the year until the end of the year through the Tridharma of higher education. The implementation of lecturer activities through the Tridharma of higher education as a whole is outlined in the Lecturer Performance Targets and an evaluation will be carried out to provide an assessment of lecturers who have carried out their performance for one year.